Biology Teachers’ Worldviews on the Global Distribution and Loss of Biodiversity: A GIS-Based Mental-Mapping Approach - Fiebelkorn, Florian; Menzel, Susanne (Frontiers in Psychology, 2019)
This paper explores (1) student teachers’ mental maps of the global distribution and loss of biodiversity and (2) their perception of threatened biodiversity at the national, transnational and global levels. Data was collected from a questionnaire study of student biology teachers from Germany (n = 868) and Costa Rica (n = 284). Student teachers’ mental maps matched quite well with the scientific view. Nevertheless, they clearly showed a ‘brazilisation bias’, meaning that the first and foremost country associated with high and threatened biodiversity was Brazil. Industrialized countries were often misconceived to have a particularly threatened biodiversity. Except for Brazil (and Costa Rica in the Costa Rican sample), most students neglected a connection between a country’s high biodiversity and its high threat as proposed by the biodiversity hotspots concept. Despite this common ground, major ethnocentric distortions merged in the composite mental maps for each sample: German students had a more global perspective on biodiversity and its loss, whereas Costa Ricans students had a more localized view. Student teachers from both countries have largely overestimated the percentage of threatened plant species on a national, transnational and global level (‘overestimation bias’). In addition, the estimated percentage of threatened plant species have correspondingly increased with a greater distance from the students’ home country (‘spatial optimism bias’). Results will be discussed in terms of educational implications.